2018
DOI: 10.1002/wcc.564
|View full text |Cite
|
Sign up to set email alerts
|

Loss and damage: A review of the literature and directions for future research

Abstract: Climate change researchers argue that a residual domain exists beyond the limits of adaptation to prevent deleterious climate change impacts: this has been labeled as "loss and damage." Over the last 8 years, there has been significant growth in loss and damage scholarship thus making it imperative to take stock of what we know already and directions for future research. We undertook a quantitative review of academic publications (n = 122) in the loss and damage field to date and documented study characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 105 publications
(227 reference statements)
0
72
0
Order By: Relevance
“…Research and policy work on NELs includes concerns with loss of biodiversity, territory, cultural heritage and encompasses the emerging issue of climate-induced human mobility. While there is no official definition of L&D under the UNFCCC, current scholarly understandings of L&D often emphasise the unavoidability and irreversibility of certain climate change impacts and the role played by constraints and limits to adaptation as drivers of adverse outcomes ( McNamara and Jackson, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research and policy work on NELs includes concerns with loss of biodiversity, territory, cultural heritage and encompasses the emerging issue of climate-induced human mobility. While there is no official definition of L&D under the UNFCCC, current scholarly understandings of L&D often emphasise the unavoidability and irreversibility of certain climate change impacts and the role played by constraints and limits to adaptation as drivers of adverse outcomes ( McNamara and Jackson, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mechler et al (2019) also identify a number of ways of ‘grounding’ the ‘so far highly political debates’ associated with L&D. However, most of the analyses that suggest de-politicisation of L&D do not go further in unpacking the politics. Recent research has suggested that there is a tendency in current L&D literature to overlook the socio-historical and political determinants of the debate ( McNamara and Jackson, 2018 ). This – combined with a more general lack of research on L&D policy development in political science and in international relations – constitutes a barrier to developing a deeper understanding of the challenges in this area of global climate governance.…”
Section: Introductionmentioning
confidence: 99%
“…Discussions of rights in the context of climate change adaptation also concern the issue of loss and damage: cases where adaptation is no longer possible, or where it has failed. A detailed discussion of loss and damage is beyond the scope of this review (for overviews, see McNamara and Jackson 2019;Mechler et al 2019). Suffice it to say that many of the questions around loss and damage mirror those related to displacement and migration, notably those around loss of culture and identity and "ontological security".…”
Section: Access To Basic Rightsmentioning
confidence: 99%
“…While some studies (e.g. Doelle & Seck, 2019;McNamara & Jackson, 2019;Tschakert et al, 2019) assign specific meanings to the words 'loss' (permanent impacts) and 'damage' (reversible impacts), it would be inaccurate to conclude that the adverse effects of climate-related stressors, reported in WGII AR5, tend to be irreversible. For example, when adverse effects of climate change on livelihood security are discussed, the authors usually speak of 'loss of livelihood' without implying that livelihoods are lost forever.…”
Section: Loss and Damage By Wgii Ar5 Chaptermentioning
confidence: 99%